2019
DOI: 10.22347/2175-2753v11i33.2217
|View full text |Cite
|
Sign up to set email alerts
|

MACE: Medida de Avaliação da Composição Escrita no ensino básico português

Abstract: As a communication and learning system, writing plays a central role in various contexts, and its teaching occurs during several years of schooling. However, writing assessment in Portuguese language lacks validated instruments. Thus, a study of accuracy and validation of the Written Composition Assessment Measure (MACE), a measure of observation built to evaluate the written composition of narrative texts in elementary education, was carried out. A total of 280 students from the 3 rd and 4 th grade of public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this study, to test inter-rater reliability, 10% of the texts produced were randomly selected and scored by four independent raters, and the Intraclass Correlation Coefficient (ICC) was calculated for each criterion and total scale (ICC total_scale = .95, range from .81 to .91 within each criterion) indicating an "almost perfect" agreement (Landis & Koch, 1977). Following an exploratory analysis explaining 61.56% of the variance (Oliveira et al, 2019), a confirmatory factor analysis revealed good fit of the model, complying with the literature's cut-off recommendations (Hooper et al, 2008), namely χ 2 = 9.818, p > .05, χ 2 /df = 1.40, CFI = .99, TLI = .99, SRMR = .02, RMSEA = .04.…”
Section: Spontaneous Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, to test inter-rater reliability, 10% of the texts produced were randomly selected and scored by four independent raters, and the Intraclass Correlation Coefficient (ICC) was calculated for each criterion and total scale (ICC total_scale = .95, range from .81 to .91 within each criterion) indicating an "almost perfect" agreement (Landis & Koch, 1977). Following an exploratory analysis explaining 61.56% of the variance (Oliveira et al, 2019), a confirmatory factor analysis revealed good fit of the model, complying with the literature's cut-off recommendations (Hooper et al, 2008), namely χ 2 = 9.818, p > .05, χ 2 /df = 1.40, CFI = .99, TLI = .99, SRMR = .02, RMSEA = .04.…”
Section: Spontaneous Planningmentioning
confidence: 99%
“…Written Composition Assessment Measure (WCAM). The WCAM (Oliveira et al, 2019) was used to assess the mechanical and content-related aspects of the writing quality. The WCAM (ω T1 = .93; ω T2 = .90) was designed on the basis of the Wechsler Individual Achievement Test (WIAC-IIUK) and includes analytical measures of both mechanical (e.g., punctuation, grammar, and spelling) and contentrelated (vocabulary, organization, ideas, and overall structure) writing skills (Dunsmuir et al, 2015;Wechsler, 2005).…”
Section: Spontaneous Planningmentioning
confidence: 99%